Wawwu Ats-Tsamaniyah: Ditinjau dari Perspektif Bahasa Arab dan Ilmu Tafsir - Samsurizal, Samsurizal; Saputra, Edriagus (Institut Agama Islam Sumatera Barat, 2023)
This study attempts to decipher one letter of the Arabic alphabet, namely the letter wawwu. The background of this paper to be is the author finds in Arabic grammatical sources and interpretations of the verses of the Qur'an various kinds of wawwu as well as their functions and uses. The author finds both Arabic language rules and interpretation rules by referring to Arabic grammar books and commentary books, namely wawwu as aljar, al`athaf, alqasam, wawwu za'idah, wawwu Hakim and lastly wawwu altsamaniyah. The references in this paper are Arabic grammar and Al-Qur'an Tafsir both primary and secondary. The qualitative descriptive research method is expected to be able to explain related to wawwu atstsamaniyah from the perspective of Arabic and the science of interpretation. From the intended method it was found: first, Wawwu atsTsamaniyah is linked to the tradition of expressing the Arabic language. Because of the habit of the Arabs to call the eighth number using wawwu altsamaniyah. Second, if the Qur'an mentions the eighth maratib by using this, to glorify and perfect his pleasure in the form of a very big reward (heaven). Third, showing a perfect and special message. This is also called alwawu ?alza'idah or wawwu za'idah as a statement amplifier.